In vitro multiplication and rooting of grapevine: Culture media and plant growth regulators - Nascimento, Daniele Camargo; Dini, Maximiliano; Sampaio, Norton Victor; Schuch, Márcia Wulff (Plant Cell Culture & Micropropagation - ISSN 1808-9909, 2019)
Micropropagation is a technique that allows to obtain quality plants, making it an important tool in the production of grapevine matrices. Composition of the culture media and plant growth regulators are commonly tested to adapt micropropagation protocols. The objective of this study was to test concentrations of Murashige & Skoog (MS) culture media and BAP (6-benzylaminopurine) and IBA (indolbutyric acid) plant growth regulators in the multiplication and in vitro rooting stages as part of the elaboration of a Chardonnay grapevine micropropagation protocol. In both experiments, multiplication and rooting, the experimental design was completely randomized, with a bifactorial scheme, testing culture media (MS and MS/2) and BAP concentrations (0; 5; 10 μM) in the multiplication and of IBA (0; 0.5; 1.0; 1.5 μM) in rooting. For multiplication, the best results for number of buds, leaves and shoots were obtained with 10 μM BAP, and the concentrations of the culture media had no significant effect for most of the variables. For rooting, the MS media provided better results. In relation to IBA, the number and average root length were influenced by the concentration used, with 0.5 and 1.0 μM providing the best results. Grapevine explants may be multiplied in MS/2 media supplemented with 10 μM BAP and subsequently rooted in MS media with 0.5 μM IBA. Index terms: Vitis vinifera; tissue culture; micropropagation; cytokinin; auxin.